Floral phytochemistry: exploring the extraction and utilization of volatile organic compounds - S. Nandhini; G. Ashokkumar; C. Indu Rani; P. Boominathan; K. Gurusamy; S. T. Bini Sundar (Discover Applied Sciences)
Abstract Floral Volatile organic compounds (VOCs) represent a diverse group of aromatic molecules crucial for plant biology, ecology, and industrial sectors. The synthesis pathways of terpenoids, benzenoids, and fatty acid derivatives within floral tissues are complex and contribute to the rich diversity of floral scents. Extraction techniques such as solvent extraction, headspace analysis, and solid-phase microextraction enable the isolation of these compounds for analysis and industrial utilization. Aroma profiling plays a pivotal role in characterizing floral VOC compositions and elucidating their roles in plant-pollinator interactions and defence mechanisms. Knowledge on VOCs not only enhances our understanding of plant physiology and ecology but also aids in fragrance development across various industries. The industrial application of floral VOCs is extensive. In cosmetics, these compounds are utilized for their aromatic properties in perfumes, lotions, and skincare products, thereby enhancing their market appeal. Pharmacologically, floral VOCs exhibit diverse bioactivities, offering potential therapeutic applications in pharmaceutical formulations, including antimicrobial, anti-inflammatory, and antioxidant properties offering potential therapeutic applications in pharmaceutical formulations. This review serves as a succinct introduction to the multifaceted world of floral volatile organic compounds, highlighting their significance and potential for future research and innovation. Graphic abstract